Transverse genicular ligament of the knee in human- A cadaveric Study - Chalise, Usha; Lama, Chhiring Palmu; Karki, Deepika; Dhungel, Shaligram (Nepal Medical College Journal, 2022)
The transverse genicular ligament is an anatomical structure present in knee connecting the anterior horns of the menisci. It is not present in all the individual. Hence this study aimed to observe the occurrence and variations of transverse genicular ligament of human knee. A descriptive observational study was planned and conducted in the Department of Anatomy of Nepal Medical College and Teaching Hospital in 15 male cadavers from June 2021 to December 2021. The ethical approval was taken from Institutional Review committee (IRC) of the Nepal Medical College and Teaching hospital (Ref no: 004-078/079). In present study, 15 male cadavers were observed. The presence of transverse genicular ligament was observed in 28 knee samples and absent in 2 samples. The knee joint with meniscal attachment of this ligament was observed in 12 (80.0%) of left knee and 13 (86.6%) in the right knee. Therefore, the menisco-meniscal pattern of attachment was the primary pattern of attachment of transverse genicular ligament in this study.